Studi Fenomenologi Perilaku Belajar Anak di Komunitas Belajar Sahabat Pelangi Manado TPA Sumompo - Putri Ireine Inri Wungow; Deetje J. Solang; Gloridei L. Kapahang (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2025)
This study aims to provide an overview of children's learning behavior, the factors influencing it, and how the subjects interact with tutors and peers in the teaching and learning process within the non-formal learning community Sahabat Pelangi in Manado. The research specifically compares children who are still attending school with those who have dropped out. A qualitative approach was employed using a phenomenological method. The researcher served as the main instrument to explore the children's subjective learning experiences. The research subjects consisted of two 11 y ear old children with different educational backgrounds. Data collection techniques included observation, in-depth interviews, and documentation. The data were analyzed using Miles and Huberman's model, which involves data reduction, data display, and conclusion drawing. Observations were conducted in social situations within the non-formal learning environment. The results show that children's learning behavior is influenced by motivation, environmental support, and the educational structures available to them. Children who are still in school tend to demonstrate more independent, structured, and active learning behaviors, supported by the roles of family and school. In contrast, children who have dropped out of school show a high but unstable interest in learning and rely heavily on the community as an alternative learning space. This study highlights the importance of learning communities as a form of inclusive education, particularly for children living in vulnerable social and economic conditions